Two decades of new panchayati raj in Karnataka : issues, options, and lessons - Mathew, George, 1943-; Institute of Social Sciences (New Delhi, India) (New Delhi Published for Institute of Social Sciences by Concept Publishing, 2011)
Papers presented at a national seminar held at Delhi during 26-27 October 1985.
section 1. Inaugural session -- section 2. Panchayati raj in Karnataka : yesterday, today and tomorrow -- section 3. Special session : Panchayati raj : Jammu & Kashmir, Karnataka -- section 4. Karnataka : Panchayati raj elections -- section 5. Karnataka innovative practices -- section 6. Concluding session.
Includes index.
Keywords: Panchayat -- India -- Karnataka -- History -- Congresses; Rural development -- India -- Karnataka -- Congresses